Identification of Novel PROP1 and POU1F1 Mutations in Patients with Combined Pituitary Hormone Deficiency - Birla, S.; Khadgawat, R.; Jyotsna, V. P.; Jain, V.; Garg, M. K.; Bhalla, A. S.; Sharma, A. (Hormone and Metabolic Research, 2016)
Growth hormone deficiency (GHD) results from variations affecting the production and release of growth hormone (GH) and is of 2 types: isolated growth hormone deficiency (IGHD) and combined pituitary hormone deficiency (CPHD). IGHD results from mutations in GH1 and GHRHR while CPHD is associated with defects in transcription factor genes PROP1, POU1F1, and HESX1. The present study reports on screening of POU1F1, PROP1, and HESX1 in CPHD patients and the novel variations identified. Fifty-one CPHD patients from 49 unrelated families clinically diagnosed on the basis of biochemical and imaging investigations along with 100 controls were enrolled. Detailed family history was noted from all participants and 5 ml blood samples drawn were processed for DNA isolation followed by direct sequencing of POU1F1, PROP1, and HESX1genes. Of the 51 patients, 8 were females and 43 were males. Mean height standard deviation score (SDS) and weight SDS were −5.50 and −2.76, respectively. Thirty-six of the 51 patients underwent MRI of which 9 (25%) had normal pituitary structure and morphology while 27 (75%) showed abnormalities. Molecular analysis revealed 10 (20%) patients to have POU1F1 and PROP1 mutations/variations of which 5 were novel and 2 previously reported. No mutations were identified in HESX1. The novel variations identified were absent in the 100 healthy individuals screened and the control database Exome Aggregation Consortium (ExAC). Reported POU1F1 and PROP1 mutation hotspots were absent in our patients. Instead, novel POU1F1 changes were identified suggesting existence of a distinct mutation spectrum in our population.
Keywords: CPHD; genetics; mutations; novel findings